Effect of barbed suture vs. conventional suture on postoperative recovery and uterine integrity in patients undergoing laparoscopic myomectomy - Fan, Lixin; Hu, Fengjiao; Zhang, Jingwei; Gao, Yanlei; Kang, Fei; Zhao, Qian (Frontiers in Surgery, 2025)
BackgroundUterine fibroids are common benign tumors in women, and laparoscopic surgery is one of the main treatment methods. The choice of suturing technique can influence postoperative recovery and uterine integrity.MethodsThis retrospective study included 210 patients who underwent laparoscopic myomectomy, divided into a barbed suture group (n = 105) and a conventional suture group (n = 105) based on the suturing method. Univariate analyses compared demographic characteristics, clinical features, postoperative recovery indicators, uterine integrity assessments, wound complications, and laboratory parameters between the two groups. Multivariate logistic regression was used to evaluate the effects of suture method and baseline characteristics on uterine integrity, as well as interactions between suture method and patient factors. Quality of life scores at 1, 3, and 6 months postoperatively were also analyzed.ResultsThe barbed suture group showed significantly better postoperative recovery and uterine integrity indicators compared to the conventional suture group (P < 0.05). Although the incidence of wound complications was lower in the barbed suture group, the difference was not statistically significant. On postoperative day 2, the barbed suture group had lower white blood cell counts (P = 0.039), higher hemoglobin levels (P = 0.029), lower pain scores (P < 0.001), and higher SF-36 quality of life scores (P < 0.001). Multivariate regression analysis revealed that history of abortion, number of fibroids, and menopausal status significantly affected uterine integrity, and barbed sutures significantly improved postoperative uterine integrity (OR = 3.984, P = 0.019). Significant interactions existed between suture method and history of abortion as well as fibroid degeneration, with barbed sutures having a more pronounced effect on uterine integrity in patients without abortion history and fibroid degeneration. Quality of life scores during postoperative follow-up were significantly higher in the barbed suture group.ConclusionBarbed suturing is superior to conventional suturing in laparoscopic myomectomy, effectively promoting postoperative recovery, improving uterine integrity, and enhancing long-term quality of life. Its benefits are more pronounced in patients without a history of abortion and without fibroid degeneration. Further large-scale randomized controlled trials are warranted to validate these findings and explore underlying mechanisms.